Animation Workshop - Public Primary Education, Cyprus Pedagogical Institute, Ministry of Education and Culture - Sofokleous, Konstantina (My University, 2026)
Animation and Drawing process analyzed and taught, based on the artist’s Animation ‘Alice’s Adventures in Wonderland’ that represented Cyprus at the 51st Venice Biennale International Art Exhibition, Italy